2002
DOI: 10.1063/1.1464660
|View full text |Cite
|
Sign up to set email alerts
|

Preferential formation of Al–N bonds in low N-content AlGaAsN

Abstract: The bonding of nitrogen in low N-content AlxGa1−xAs1−yNy with x⩽0.05 and y⩽0.04 has been studied by Raman spectroscopy. Upon the addition of Al to GaAsN, additional vibrational modes are observed at around 450 cm−1, which is below the GaN-like longitudinal optical (LO) phonon mode centered at 470 cm−1. These modes are attributed to the formation of Al and N containing complexes with Al-to-N bonding. With increasing Al content the Al–N related modes gain intensity at the expense of the GaN-like mode, and they b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
7
38
0
Order By: Relevance
“…They are therefore related to the simultaneous presence of N and Al. Vibration modes near 400 and 450 cm -1 have been reported [4,18] in the room temperature Raman spectra of AlGaAsN films, which are attributed to the preferential Al-N bonding [4]. In our case, this can be interpreted as an indication of nitrogen migration towards the MQW interfaces.…”
Section: Resultssupporting
confidence: 63%
“…They are therefore related to the simultaneous presence of N and Al. Vibration modes near 400 and 450 cm -1 have been reported [4,18] in the room temperature Raman spectra of AlGaAsN films, which are attributed to the preferential Al-N bonding [4]. In our case, this can be interpreted as an indication of nitrogen migration towards the MQW interfaces.…”
Section: Resultssupporting
confidence: 63%
“…Raman scattering and photoluminescence (PL) results strongly suggested that most of the N atoms form Al-N bonds instead of Ga-N bonds [2]. Recently, Geppert et al have also reported similar results through their Raman characterization of the RF-MBE grown AlGaAsN with low Al amount (Al: 0-5%, N: 0-4%) [3]. However, we need more detailed information about the local lattice structures in the region with widely varying Al amount to make clear the structural change due to the Al-N bond formation.…”
supporting
confidence: 58%
“…Of these, only the one at 473 cm -1 also occurs in ternary Ga(As,N) [9] and originates from localized vibrations of Ga 4 N units. Features at 327, 348, 385, 400, 451, 458 and 500 cm -1 are obviously linked with a simultaneous presence of Al and N and therefore originate from AlN-like or AlGaN mixed complexes [4]. Going from Ga 0.95 Al 0.05 As 0.995 N 0.005 to Ga 0.95 Al 0.05 As 0.97 N 0.03 causes a significant increase of the GaN-like mode intensity relative to the AlN-like ones.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we study the influence of N incorporation and subsequent hydrogenation on the properties of Ga-rich (Ga,Al)As. While a considerable amount of information is already available on the local vibrational properties of N impurities in (Ga,Al)As [4], rather little is known about the possible effect of the observed non-statistical binding behaviour of N on the electronic band structure of this quaternary alloy.…”
Section: Introductionmentioning
confidence: 98%